2013
DOI: 10.1177/0363546513501795
|View full text |Cite
|
Sign up to set email alerts
|

Suture Anchor Fixation of Bony Bankart Fractures

Abstract: This study will aid in the selection of the optimal repair technique for bony Bankart fractures by providing important insights into the quality of initial fixation and ultimate strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…Regarding the strengths of 1-point versus 2-point fixations, Giles et al. 10 performed a biomechanics study and found equivalent failure strengths and load transfers for the 2 groups. The suture bridge technique may provide greater initial fracture stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the strengths of 1-point versus 2-point fixations, Giles et al. 10 performed a biomechanics study and found equivalent failure strengths and load transfers for the 2 groups. The suture bridge technique may provide greater initial fracture stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported techniques have yielded good results; however, fixation through the bony fragment might result in the fragment fracturing, making the surgery more complicated. Regarding the strengths of 1-point versus 2-point fixations, Giles et al 10 . performed a biomechanics study and found equivalent failure strengths and load transfers for the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Existen escasos estudios biomecánicos que hayan intentado comparar las diferentes técnicas. Giles et al 46 compararon las técnicas de Sugaya et al 7 y BBB para defectos de 15% en 16 especímenes cadavéricos, y demostraron que la técnica BBB, con doble punto de fijación, proporciona significativamente mayor estabilidad del fragmento frente a cargas concéntricas y excéntricas en comparación a la técnica de Sugaya et al, 7 con un solo punto de fijación ( p < 0,04), pero sin diferencias en transferencias de carga y superficie de contacto. Spiegl et al 2 realizaron un estudio similar, pero con defectos glenoideos > 25%.…”
Section: Estudio Biomecánicosunclassified
“…There are few biomechanical studies that have tried to compare the different techniques. Giles et al 46 compared the Sugaya et al 7 and BBB techniques for 15% defects in 16 cadaveric specimens, demonstrating that 2-point fixation techniques provide significantly greater fragment stability against concentric and eccentric loads compared to the Sugaya et al 7 technique, with 1 point of fixation ( p < 0.04), but without differences in load transfers and contact surface. Spiegl et al 2 performed a similar study, but with glenoid defects > 25%.…”
Section: Biomechanical Studiesmentioning
confidence: 99%
“…Andere Autoren konnten im biomechanischen Modell signifikante Stabilitätsverluste ab einer Defektgröße zwischen 15 und 20% nachweisen [32,33]. In den eigenen biomechanischen Versuchen zeigte sich zusätzlich ein deutlicher Zusammenhang zwischen dem Instabilitätsausmaß und dem Grad der Labrumablösung, die über die Frakturgrenze hinaus nach kranial und kaudal reicht [34]. Da dies in den biomechanischen Studien nicht berücksichtigt wurde, gehen wir davon aus, dass bei entsprechender zusätzlicher Labrumablösung eine Instabilität ab einer ossären Bankart-Läsion von 15-20% zu erwarten ist.…”
Section: Abb 3 8 Algorithmus Zur Klassifikation Ossärer Bankart-läsiunclassified